AGING AND URBAN AGGLOMERATION UNDER A MULTI‐REGIONAL OVERLAPPING GENERATIONS MODEL. Issue 2 (14th June 2017) - Naito, Tohru; Omori, Tatsuya
Abstract : We develop a two‐region model in an overlapping generations economy with longevity, assuming that households decide the number of children and the residential location. An examination of the relationship between life expectancy and spatial agglomeration leads to our conclusion that a longer life expectancy promotes agglomeration. The results of our study show that the imbalance of the population distribution between urban and rural areas grows concomitantly with longevity.